Investigation of RSA Digital Signature Scheme Working in Digital Envelope Algorithm - Vobolis, A.; Nefas, P. (Elektronika ir Elektrotechnika, 2003)
Digital envelopes were invented to obtain the advantage of secret and public key cryptographies. In practice public-key algorithmswhich increase security are used together with secret key algorithms which increase encryption speed in such called “digital envelope”principle. The algorithm of digital envelope successfully can be used in RSA digital signature scheme. Entity A signs the message andencrypts it with entities B public key. Entity B receives the message and decrypts it with its private key and verifies authenticity ofdigital signature. Using RSA digital signature scheme working in digital envelope algorithm in case of different modules sizes reblockingproblem can occur. To solve re-blocking problem we can use such solutions as reordering, using two modules or prescribingthe modules form. Bibl.5 (in Lithuanian, summaries in Lithuanian, English, Russian).